Magnetostratigraphic evidence for the occurrence of pre-Brunhes (>780 kyr) sediments in the northwestern part of the Kathmandu Valley, Nepal (Journal of Nepal Geological Society, 2001)
Fine-grained silt/clay sediments constituting several sections of the fluvio-lacustrine sediments distributed in the central and northwestern parts of the Kathmandu Valley have been studied for the magnetic polarity stratigraphy. These sediments carry a stable primary remanence, residing in hematite and/or magnetite, which is isolated after alternating field demagnetization above 25- 30 mT. The sediments below the Thimi geomorphic surface show dominantly normal polarity except for a short reverse polarity event near the base probably attributable to the Laschamp event (39-45 Ka). In the northwestern part, a prominent reverse polarity magnetozone occurs within the lower parts of the sections that are exposed below the Gokarna geomorphic surfaces. This implies to the deposition of the sediments yielding the reverse polarity prior to the Brunhes Normal Polarity Chron (i.e. before 780,000 yrs). This new discovery requires a thorough chronological study of the northern part of the valley with regard to the extent and distribution of such old deposits, which may directly correlate to the Lokundol Formation occurring widely in the southern part of the Kathmandu Valley.